Assessment of Obstetric Outcomes in Pregnancy-Induced Hypertension - Nusrat Fozia Pathan, Aliya Hafeez, Hafsa Mubashir, Munawar Afzal, Bushra Noor Khuhro, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregnancy-induced hypertension is a significant obstetric complication that adversely affects maternal and neonatal outcomes. Objective: To assess the obstetric outcomes associated with pregnancy-induced hypertension and evaluate the relationship between the severity of pregnancy-induced hypertension and maternal-fetal complications. Methodology: This comparative observational study was conducted at Obstetrics & Gynecology, Shifa International Hospital Faisalabad during January 2023 till July 2023. A total of 178 pregnant women diagnosed with PIH were included in the study. Data were collected through patient interviews, clinical examination, review of antenatal records, and delivery notes. Results: 57.3% had mild pregnancy-induced hypertension and 42.7% had severe pregnancy-induced hypertension. Cesarean section was performed in 61.8% of cases, primarily due to fetal distress and failed induction. Maternal complications included postpartum hemorrhage (7.3%), abruptio placentae (3.9%), and HELLP syndrome (3.4%). One maternal death was recorded. On the fetal side, preterm births occurred in 43.8% of cases, low birth weight in 53.9%, intrauterine growth restriction in 20.8%, and neonatal intensive care unit admissions in 32.6%. Severe pregnancy-induced hypertension was significantly associated with higher rates of these adverse outcomes (p <0.05). Conclusion: Pregnancy-induced hypertension is strongly associated with increased maternal and neonatal morbidity. The severity of pregnancy-induced hypertension correlates significantly with the likelihood of complications such as preterm delivery, low birth weight, and operative delivery. Early detection and timely intervention are essential to improve pregnancy outcomes and reduce associated risks. Keywords: Assessment, Outcome, Pregnancy induced hypertension, Maternal-fetal complication